Harmonic Capabilities and their Relationship to the Planned Behavior of Iraqi National Futsal Team Players - Hawail Farhan Alkabi, Abdullah; Dia'Hasan, Ruya; Abdul Wahid Jassim, Rana (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the harmonic capabilities as well as the level of creative Planning behavior for the research sample, as well as the relationship between the level of harmonic capabilities and creative Planning behavior for football halls players. The tests used in the study were conducted, the researchers conducted statistical treatments and obtained the results, and through them the researchers reached the following conclusions: 1. That all parties had a high correlation with the level of creative Planning behavior, in which the diverse training aspect must be taken care of so that there is creativity because brain control relies on understanding and perception and not on memorization in decision-making. The most important recommendations: • That all harmonic traits are directly related to the level of creative Planning behavior through the level, mental abilities to analyze information for the research sample. The most important recommendations were • That all consensual capabilities depend directly on the nervous directives that come from the brain to the kinematic limbs and control them, which creates a state of creative Planning behavior that leads to the creation of a state of creativity.